Formation, Structures and Electronic Properties of Silicene Oxides on Ag(111). Issue 7 (July 2017) - Ali, Muhammad; Ni, Zhenyi; Cottenier, Stefaan; Liu, Yong; Pi, Xiaodong; Yang, Deren
Abstract : The formation, structural and electronic properties of silicene oxides (SOs) that result from the oxidation of silicene on Ag(111) surface have been investigated in the framework of density functional theory (DFT). It is found that the honeycomb lattice of silicene on the Ag(111) surface changes after the oxidation. SOs are strongly hybridized with the Ag(111) surface so that they possess metallic band structures. Charge accumulation between SOs and the Ag(111) surface indicates strong chemical bonding, which dramatically affects the electronic properties of SOs. When SOs are peeled off the Ag(111) surface, however, they may become semiconductors.